Garlic nutrient management in Ethiopia - a review - Shiferaw, G Diriba- (Journal of Spices and Aromatic Crops, 2016)
The main aim of this review is to provide an overview of the garlic crop productivity and its production management requirements like soil, climate and fertilization in general and specifically in Ethiopia, comparing them with current research trends and to indicate future benefits of soil nutrient management investigations. The application of balanced nutrients under optimum moisture availability in different soil types is an important crop management strategy, which may help maximizing crop yield and quality. Also, lack of optimum nutrients and moisture in the soil has been the major bottlenecks of garlic production and productivity; since the crop has a very shallow root system that requires frequent irrigation and fertilization with different types of fertilizers under various soil types. Low soil fertility is one of the principal and pervasive constraints to garlic production in Ethiopia; thus, there are differences among soil types in yielding ability under different nutrients and soil characteristics. Most smallholder farmers in Ethiopia appreciate the value of fertilizers, but they seldom apply them at the recommended rates and at the appropriate time according to the soil characteristics. These are because of high cost, lack of credit, delivery delays, and low and variable returns. In addition, the traditional organic inputs, like crop residues and animal manures, it cannot meet crop nutrient demand over large areas because of the limited quantities available, the low nutrient content of the materials, and the high labor demands for processing and application. However, it is possible to increase garlic crop yields through identification/selection of soil type and balanced nutrients application or searching for other nutrients sources beyond Urea and Diammonium phosphate especially in Ethiopian condition. Therefore, the integrated use of both the organic and inorganic fertilizers was felt as the best option to increase both yield potential and quality of garlic crop.